THE RELATIONSHIP FREQUENCY OF DRINK COFFEE WITH BLOOD PRESSURE IN HYPERTENSION PATIENTS IN CANGKRING VILLAGE, SIDOKARE DISTRICT, SIDOARJO DISTRICT, SIDOARJO DISTRICT: THE RELATIONSHIP FREQUENCY OF DRINK COFFEE WITH BLOOD PRESSURE IN HYPERTENSION PATIENTS IN CANGKRING VILLAGE, SIDOKARE DISTRICT, SIDOARJO DISTRICT, SIDOARJO DISTRICT - Ilmi, Miftakhun Nafidatul; Roni, Faishol; Puspitasari, Ika (WELL BEING, 2020)
Hypertension often does not cause symptoms, while persistently high blood pressure in the long term can cause complications, namely, damage to the kidneys, heart, and brain. Consumption of caffeinated coffee can increase the risk of pressure. blood namely hypertension. The aim is to determine the relationship between coffee drinking frequency and blood pressure in patients with hypertension in the Cangkring sub-village of Sidokare, Sidoarjo Sub-district, Sidoarjo Regency. The study design uses cross-sectional. The population was 40 and samples were taken by 36 respondents with total sampling techniques. This research instrument uses checklist sheets and observation sheets. Based on the research results of Coffee Drinking Frequency found in Cangkring Hamlet, Sidokare Subdistrict, Sidoarjo Subdistrict, Sidoarjo Regency, most rarely 29 respondents (80.6%) Hypertension was found in Cangkring Hamlet, Sidokare Subdistrict, Sidoarjo Subdistrict, Sidoarjo Regency, most of Stage 1 hypertension was 23 respondents (63, 63 9%). Data analysis using the Spearman Rank Test with p-value is 0.139 because the p-value is 0.005 then H1 is rejected, which means there is no relationship between coffee drinking frequency and blood pressure in hypertension sufferers.